Penanganan Ansietas Dengan Cara Hipnotis Lima Jari Dan Mendengarkan Musik Pada Penderita Diabetes Mellitus Tipe 2 Dan Gagal Ginjal Kronik Di Rsmm - Lidia Simatupang; Yossie Susanti Eka Putri (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2015)
Anxiety nursing care for type diabetes mellitus. Physical problems often accompanied by psycosocial problems and cause ineffectiveness of medical therapy to physic.This suggests that psycosocial health is very important to the health of client and if ignored will cause delay healing and increase the risk of complication. One of the psycosocial problem is anxiety which psycosocial problems signed by discomfort and worry feeling and the cause is often unknown. This work aims to describe anxiety nursing care on Mr. P experiencing type two diabetes mellitus with complications chronic renal failure. Intervenstion was given during six days. The interventions were five fingers hynotic and listening music. The results showed that problem solves by five fingers hypnotic and music marked by decrease of signs and symptoms of anxiety on Mr. P. It was conclude that five fingers hypnotic and listening music could reduce anxiety for type 2 diabetes mellitus with complications chronic renal failure.